Human Resources Development and Those Left Out: Contribution of Universal Policies - Zoe A. Karanikola; George A. Panagiotopolos (European Scientific Journal, ESJ, 2020)
This paper focuses on exploring the thematic analysis of the text “Human Development Report” (United Nations, 2016) about the way universal policies can contribute to the development of all left out. This means people that belong to vulnerable groups. What are their characteristics, what are their targets, and how can they be implemented? According to the findings, universalism is the principle of the human development approach, but it is not enough. It is necessary to be translated into practice by identifying and breaking down barriers that exclude certain groups. Some universal policies need to be reoriented, since there are many disparities. Even though human development can be achieved, it does not mean that it can also be sustained. Progress may be slowed or even reversed. In such context, people must get empowered even if policies and the relevant actors fail to deliver. They will get stronger when they demand their rights, raise their voice, and seek to redress one situation. Policies should also be inclusive which involves formulating an employment – led growth strategy. This should be done with emphasis on creating productive and remunerative employment opportunities in sectors where poor people live and work, enhancing inclusion in productive resources, and under taking high-impact multidimensional interventions. The usefulness of this study lies in the fact that it provides useful information about United Nations’ efforts and policiesto help all people to develop. These efforts and policies can be compared to those of other European and international organizations such as the Council of Europe and the Organization for Economic Co-operation and Development (OECD). This helps in creating larger databases that can multiply and become indicators of relevant actions at both regional and global level.